The Effect of Servant Leadership, Employee Engagement and Work Stress on Work Safety with Contractor Safety Management System (CSMS) Mediation in the Oil and Gas Industry - Ahmad, Ahmad; Anshar Daud; Arie Wibowo Khurniawan (Jurnal Ekonomi, 2024)
The Oil and Gas Industry (MIGAS) is a vital economic sector, but it faces high risks related to occupational safety and health. Workplace accidents in MIGAS can have serious consequences. In an effort to manage occupational safety in this sector, the Contractor Safety Management System (CSMS) plays a central role. Additionally, variables such as servant leadership, employee engagement, and work stress also have significant impacts on the level of occupational safety. This research aims to fill the knowledge gap regarding the influence of these variables, with CSMS serving as a mediator. The results of the Structural Equation Modeling Partial Least Square (SEM PLS) analysis indicate that Servant Leadership, Employee Engagement, work stress, and the Contractor Safety Management System (CSMS) positively and significantly influence the level of occupational safety. Furthermore, Servant Leadership, Employee Engagement, and work stress also have a positive and significant impact on CSMS. The key finding of this research is that CSMS acts as a mediator between Servant Leadership, Employee Engagement, work stress, and the level of occupational safety. The outcomes from the Focus Group Discussion (FGD) reveal that enhancing management commitment, improving training programs, and strengthening partnerships with contractors can substantially enhance occupational safety in specific industries, particularly in the context of the high-risk Oil and Gas industry. This conclusion provides a comprehensive view of the influencing factors and applicable strategies to improve occupational safety in this high-risk industry sector